Koordinasi Pemerintah Desa dalam Penyusunan Rencana Kerja Pemerintah Desa di Desa Tamiajeng Kecamatan Trawas Kabupaten Mojokerto - Feby Nurrahma Wardani; Lukman Arif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The implementation of a village government work plan can run well because it is based on coordination and cooperation between the village government and the activity implementer. In this research, the researcher will use descriptive qualitative research, because the researcher wants to describe and describe in detail the phenomena or problems raised. The location of this research was conducted in Tamiajeng Village, Trawas District, Mojokerto Regency. The focus of this research is on vertical, horizontal and functional coordination in preparing the Village Government Work Plan in Tamiajeng Village. The sources of informants in this research were the Village Head, Head of the Village Development Planning Section, Village Secretary, and Village Staff/Apparatus involved in preparing village government work plans. Data collection techniques, such as Interviews, Questionnaires and Observations. Techniques for testing data validity in qualitative research, namely trustworthiness, transferability, dependability and conformability. Data analysis techniques use data reduction, data collection, data presentation and conclusions. The research results show that the coordination carried out by the Tamiajeng village government as a whole has gone quite well, both vertically, horizontally and functionally. Community participation is quite active in musrembangdes activities to voice aspirations. The key to success in coordinating the preparation of RKPDes for Tamiajeng village is communication, collaboration and cooperation between village institutions and village communities.